Evaluating the Effect of Circ-Sirt1 on the Expression of SIRT1 and Its Role in Pathology of Pulmonary Hypertension. (February 2022) - Diao, Wenjie; Liu, Ge; Shi, Chao; Jiang, Yiyao; Li, Haihui; Meng, Jinjin; Shi, Yu; Chang, Mingming; Liu, Xuegang
Pulmonary arterial hypertension (PAH) is a disease that plagues a major portion of the world's population, and there is currently no effective cure for this ailment. The proliferation and migration of pulmonary artery smooth muscle cells (PASMC) are known to be the pathological basis of pulmonary vascular remodeling in pulmonary hypertension. Studies in the past have shown involvement of CircRNA in the pathology of pulmonary as well as cardiovascular diseases. However, there are very few studies that have analyzed the relationship between CircRNA and PAH. The aim of this study was to explore this relationship by using rat PAH model. A hypoxic, PAH rat model was constructed for this study and the subsequently produced hypoxia-induced rat PASMC cells were utilized to demonstrate the reduction in expression of circular RNA of Silent information regulator factor 2-related enzyme 1 (circ-Sirt1) and SIRT1 mRNA in response to hypoxia, through cell function tests, cell rescue tests, and physical tests. We found that the expression of circ-Sirt1 and SIRT1 decreased in the PAH rat model induced by hypoxia. It was also revealed that the overexpression of circ-SIRT1 increased SIRT1 levels, but inhibited the expression of transforming growth factor (TGF)-β1, Smad3, and Smad7, and weakened PASMC cell vitality, proliferation, and migration ability. The findings of the present study indicate that circ-Sirt1 regulates the expression of SIRT1 mRNA and inhibits TGF-β1/Smad3/Smad7 mediated proliferation and migration of PASMC. This provides a new insight into the molecular mechanism of pulmonary artery vascular remodeling in PAH and may aid in the development of novel therapeutic options for management of PAH.